Pembibitan Ternak Sapi Potong dalam Sistem Integrasi Tanaman – Ternak di Kawasan Pantai Selatan Kabupaten Bantul - Soeharsono Soeharsono; Sinung Rustijarno; Kurnianita Triwidyastuti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2008)
This research aimed to know the management effort beef cattle breeding in the integrate crop - livestock system in  south coastal area Bantul regency of Yogyakarta Special Region. Farm Record keeping conducted livestock farmer group Andini Mukti of Poncosari village, Srandakan countryside,  Bantul regency. A number of 20 farmers grouped by as according to farming system : 1) Beef cattle breeding farming system and 2) Integrate rice crop–livestock system. Management farming and livestock noted and tabulation. Data analysed with the distribution frequency and discription. This results of research indicate that the beef cattle breeding system by ownership 2,36 cows/farmer. Beef cattle looked in group individually cage area. Hay from weste rice crop given ad libitum added consentrate mean 1,5 kg/head. Insemination system conducted with the artificial insemination made in with the S/C 2,39. Labour effusing in livestock management 114,06 work day person/farmer/year.  This result of effort in the calf and organic fertilizer. Effort income beef cattle breeding system equal Rp 3.013.000 (R/C 1,64). Integrate rice crop – livestock  with the pattern plant the paddy - paddy – crops planted. Farm ownership 1000 m2 /farmers and 2 cows which looked in cage group area. Using produce in the form of seed 45,83 kg/ha; fertilize 395,52 kg/ha and family labour 43,06 work day person and external labour 15,03 work day person every season plant. The productivity of unhulled paddy dry harvest 6,88 ton/ha. Income farming system integrate rice crop – livestock  equal to Rp 5.592.310 (R/C 1,82). Key words             : management, breeding, beef cattle, integration